Ludzie i metody. Rozbijanie podziemia niepodległościowego w Lubartowskiem (lipiec 1944 – kwiecień 1947) - Poleszak, Sławomir (Studia Polityczne, 2023)
The Lubartów district was one of the poorest areas of the Lublin province; nevertheless, strong structures of the independence underground subordinated and then reporting to the legitimate Polish government in exile were active in its area. The main crackdown on the underground occurred between August 1944 and April 1947. In the first year after the communists took power, the Soviets and the structures of the repression apparatus created in Lubartów took the main role in smashing the local underground. Its Polish officers mostly came from rural backgrounds and were poorly educated and trained. Ethnically, they were mostly Poles. However, at the District Public Security Office (PUBP) in Lubartów, two of the first three PUBP managers were Ukrainians by origin. The section that was responsible for fighting the underground was initially headed by a Jew, who was succeeded by a Ukrainian. Despite their low level of education and training, it was security office (UB) officers who were victorious in the crackdown on the local underground. Soviet assistance, violence and lawlessness guaranteed success.